Iowa Birdline update, April 5, 1993 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1993)
Email for the Iowa Birdline update for April 5, 1993. Highlights of the update include sightings of the continued presence of a Black-throated Sparrow and Townsend's Solitaire, plus a Prairie Falcon. Also included are handwritten notes for the next week's update with sightings of several Tundra Swans and three Great Egrets. Epson - sheet feed/flatbed